Paulo E Onésimo: Escravidão E Manumissão No Principado Romano - Silva, Luciano Alves [UNIFESP] (2018)
In The Present Work We Propose To Investigate A Recurrent Subject In The Pauline Letters: Slavery, Assuming That This Biblical Author Did Not Deal Directly With This Issue From The Legal Point Of View. Our Effort Then Stopped To Try To Reach The Thought Of Paul Of Tarsus On The Slavery And The Roman Manumission, Analyzing Them From The Documents Produced By Paul Himself, Other Biblical Texts, Still Others Of The Same Time With The Same Emphasis, As Well As From Other Secondary Sources And Specialized Researchers Of This Theme. The Main Document Object Of Our Investigation Is The Letter That Paul Wrote To His Friend Filemon, In Which He Intercedes For A Newly Converted Slave To Christianity, Whose Name Is Onesimus